Constructing children's physical education experiences : understanding the content for teaching. - Allison, Pamela C. (Allyn and Bacon, 2000)
Connecting what you teach to why you teach it: Constructing Meaning in Children's Education; A conceptual View of Movement. The contents of physical Education: Teaching Educational Games, Gymnastics, Dance. Preparing for Teaching and for Being a Teacher: Planning for Student Learning...